Bhinneka Tunggal Ika: Real Proof Of The Power Of Pancasila - Yuniarto, Bambang; Nisa, Dita Aulia; Setianingsih, Nur Aisyah Addiessuci; Illah, Ahmad Ridho; Ilham, Muhamad (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Indonesia is a nation rich in diversity, encompassing a variety of ethnic groups, religions, languages, and cultures. The concept of Bhinneka Tunggal Ika—"Unity in Diversity"—reflects this pluralism, advocating for peaceful coexistence despite differences, embodying the essence of Pancasila, the foundational ideology of the country. The national motto, symbolized by the Garuda Pancasila emblem, signifies the unity of the Indonesian people. This study aims to demonstrate that the challenges facing Indonesia's adherence to Pancasila can be addressed through the application of Bhinneka Tunggal Ika. Using qualitative research methods, particularly library research, data were collected from various sources including books, academic journals, and recent studies. The results emphasize that Bhinneka Tunggal Ika has long been a cornerstone of national unity and a symbol of Indonesia's rich diversity. Implementing Pancasila’s values in alignment with this motto fosters national welfare and underscores the importance of tolerance and interfaith harmony. Additionally, Bhinneka Tunggal Ika plays a vital role in raising awareness of nationalism and reinforcing societal cohesion.